EMOTIONAL TRANSFORMATION IN "A MAN CALLED OVE" - Hadziq Fikri, Arief; Kurniati, Nia; M Nur hidayat, Dayad; Adi Prayoga, Dimas; Anggatama, Rizki; Anwar, Choiril (ENGLISH JOURNAL, 2025)
This study examines the emotional transformation of the main character, Ove, in A Man Called Ove by Fredrik Backman through a literary psychology approach. The purpose of this research is to explore how Ove’s emotional journey—from being stubborn, isolated, and pessimistic to finding renewed meaning in life—is influenced by his relationships and experiences. Using a qualitative descriptive method with documentation techniques for data collection, this study analyzes key interactions, particularly with his neighbor Parvaneh and symbolic elements such as a shabby cat, as well as the impact of his past, including the loss of his wife. The findings reveal that love, social relationships, and solidarity are crucial factors in emotional healing and personal growth. This research highlights the significance of human connection in overcoming isolation and loneliness, offering valuable insights for literary studies, education, and the development of inclusive communities.